Supervising postgraduates from non-English speaking backgrounds (Buckingham : Society for Research into Higher Education and Open University Press, 1999)
This book is divided into four parts: The NESB student; Examining the issues; Establishing some principles for effective supervision; and Practical Responses.
Keywords: Graduate students; Counseling; Faculty advisors; Faculty advisors; Graduate students -- Counseling of; Students, Foreign -- Counseling; Teacher-student relationships; English language -- Study and teaching -- Foreign speakers